Daya Hambat Ekstrak Etanol Daun Suruhan (Peperomia pellucida l.) Terhadap Pertumbuhan Bakteri Penyebab Jerawat (Propionibacterium acnes) Dengan Metode Sumur Agar - Fadly Putrajaya; Nur Hasanah; Anis Kurlya (Edu Masda Journal, 2019)
Pimples or acne vulgaris are obstructive skin diseases and chronic inflamatif in pilosebaseas that often occur among adolescents. According to the Indonesian Cosmetic Dermatology Study, sufferers of acne vulgaris in 2006, 2007 and 2009 in a row as much as 60, 80, and 90%. The highest prevalence in women (14-17 years) ranges from 83-85% and in men (16-19 years) ranged from 95-100%. Therefore, there is a need for altervatives to minimize antibiotic resistance and prevent side effects from occurring. One alternative is the use of antibacterial that comes from natural ingredients. One of the natural ingredients that can be utilized is suruhan leaf (Peperomia pellucida L.). The study aims to find out the power of ethanol extract of the suruhan leaf against the growth of acne causing bacteria (Propionibacterium acnes). This research is an experimental study. The data used in this study is the diameter of the clear zone. The results of the study showed the ethanol extract of the suruhan leaf (Peperomia pellucida L.) has a barrier to acne causing bacteria (Propionibacterium acnes). At a concentration 25% (6,65 mm), (129,39 mm2) then the resistance is medium, the concertration of  50% (8,2 mm), (130,98 mm2) then the resistance is relatively medium, concentration 75% (13,7 mm), (532,42 mm2) then the resistance is relatively strong, the concentration of 100% (17,15 mm), (539,1 mm2) then the power is relatively strong. Further research is suggested, fractionation extract of suruhan leaf ethanol to know the active compounds that act as antibacterial using polar solvents and non polar solvents.